The Effect of Leadership, Job Satisfaction and Self-Efficacy on Lecturers’ Performance - Lili Salfina; Reflianto Reflianto; Asrul Asrul (Jurnal Komunikasi Pendidikan, 2022)
This study aimed to analyze the effect of leadership, job satisfaction, and self-efficacy. The method of this research was a quantitative survey method. We collected the data from a sample of the college of economic lecturers numbered 34 people using the research instrument of questionnaires. Analysis of the questionnaire used a 5-points Likert scale and a multiple linear regressions test. Research findings reported a significant influence on the leadership perception, job satisfaction, and self-efficacy of the lecturers' performing partially and simultaneously. This study contributed to head building participatory and communicative leadership in improving the planning, execution, and evaluation of learning to get the expected teaching competence. We suggest that higher education leaders always pay attention to the needs of their subordinates. Create a pleasant work atmosphere that can improve positive self-efficacy and job satisfaction.